2013
DOI: 10.1016/j.ejvs.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Indicators for Comparing the Incidence of Diabetic Amputations: A Nationwide Population-based Register Study

Abstract: The standardized, population-corrected incidence of major LEA, the minor-major LEA ratio, and major-amputation-free survival proved useful as indicators in comparing the outcomes of diabetic foot care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 15 publications
(12 reference statements)
2
22
0
3
Order By: Relevance
“…Our observation is that the decreasing incidence of major lower extremity amputations in patients with T2DM in the last 8 years of the study is consistent with most epidemiological studies from Europe and the US [8,17,[19][20][21][22][23]. Lombardo et al explained this trend, indicating that, even in presence of increased diabetes incidence and prevalence, they were eventually facing an improvement in the quality of diabetes therapy as well as in the overall approach to diabetic foot care [8].…”
Section: Discussionsupporting
confidence: 90%
“…Our observation is that the decreasing incidence of major lower extremity amputations in patients with T2DM in the last 8 years of the study is consistent with most epidemiological studies from Europe and the US [8,17,[19][20][21][22][23]. Lombardo et al explained this trend, indicating that, even in presence of increased diabetes incidence and prevalence, they were eventually facing an improvement in the quality of diabetes therapy as well as in the overall approach to diabetic foot care [8].…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, there have been a disproportionate number of studies that only included males [33, 34, 69, 70] or people with diabetes [17, 18, 27, 34, 35, 38, 58, 6264, 67, 69, 74]. While most studies reported these salient details, more detailed information about race, sociodemographic factors, or the presence of common comorbidities were reported in an ad hoc way and as such, it was not possible to make a detailed assessment of the degree to which people included in research represented the broader population of people facing PFA or TTA (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Скорректированная по популяции частота первой высо-кой ампутации на 100 тыс. пациенто-лет снизилась за ана-лизируемый период с 10,0 (95% ДИ 9,6-10,5) до 7,3 (95% ДИ 6,9-7,6) (p<0,001), а соотношение малых-высоких ампутаций показало увеличение с 0,86 (0,8-0,92) до 1,35 (1,26-1,46) (p<0,001) [12]. Наиболее важная информация, полученная в упомянутом исследовании, заключалась в значительной вариабельности данных в зависимо-сти от ареала покрытия специализированной службы, в частности, наличия положительной динамики в регио-нах ответственности университетских клиник.…”
Section: Discussionunclassified